Preparation and characterization of TiO2/carbon nanowall composite on a transparent substrate - Pierpaoli, Mattia; Lewkowicz, Aneta; Ficek, Mateusz; Ruello, Maria Letizia; Bogdanowicz, Robert (Photonics Letters of Poland, 2018)
A transparent titanium dioxide and carbon nanowall composite (B-CNW/TiO2) material was fabricated by growing boron-doped carbon nanowalls (B-CNWs) on quartz glass with microwave plasma-enhanced chemical vapor deposition technique, followed by sol-gel deposition using titanium isopropoxide as a TiO2 precursor. Different layer thicknesses were fabricated. Samples were investigated by spectroscopic ellipsometry and UV-VIS spectroscopy. Results shows how the B-CNW thickness affects the optical transmittance, bandgap and electrical conductivity. Full Text: PDF References Wang, H., Quan, X., Yu, H. & Chen, S. Fabrication of a TiO2/carbon nanowall heterojunction and its photocatalytic ability. Carbon N. Y. 46, 1126–1132 (2008). CrossRef Fujishima, A., Zhang, X. & Tryk, D. A. TiO2 photocatalysis and related surface phenomena. Surf. Sci. Rep. 63, 515–582 (2008). CrossRef Pierpaoli, M., Giosuè, C., Ruello, M. L. & Fava, G. Appraisal of a hybrid air cleaning process. Environ. Sci. Pollut. Res. 24, 12638–12645 (2017). CrossRef Sobaszek, M. et al. Diamond Phase (sp3-C) Rich Boron-Doped Carbon Nanowalls (sp2-C): Physicochemical and Electrochemical Properties. J. Phys. Chem. C 121, 20821–20833 (2017). CrossRef Lewkowicz, A. et al. Thickness and structure change of titanium(IV) oxide thin films synthesized by the sol–gel spin coating method. Opt. Mater. (Amst). 36, 1739–1744 (2014). CrossRef Tauc, J. Optical properties and electronic structure of amorphous Ge and Si. Mater. Res. Bull. 3, 37–46 (1968). CrossRef